Strategi Pengembangan Lembaga Keuangan Mikro UMKM dalam Peningkatan Daya Saing di Era Digital Kota Medan - Santi Bancin, Eliyas; Rianti, Irna; Tusa’diah Siregar, Nurhalimah; Nanda, Muhammad Rhenz; Hayati, Fitri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to identify development strategies for MSME Microfinance Institutions (LKM) in Medan City to increase competitiveness in the digital era. The research method used is descriptive qualitative. The research results show that microfinance institutions need to carry out several strategies, such as: digital transformation towards a digital ecosystem, development of digital financial products and services, increasing digital literacy of MSMEs, collaboration with various related parties, and adaptation to applicable regulations. By implementing these strategies, it is hoped that microfinance institutions can play a more effective role in supporting the growth and development of MSMEs in the digital era.